PENCEGAHAN STUNTING PADA IBU HAMIL DENGAN MEMANFAATKAN DAGING SAPI SEBAGAI BAHAN PANGAN SETEMPAT DI DESA KOTO GUNUNG, GUNUNG TOAR, KUANTAN SINGINGI - Suroyo Suroyo; Alma Febrianti; Doni Ari Saputra; Febrianda Firdaus Rahman; Ghali Mufadhol; Hanifah Rodiah; M. Farhan; Nurifadilla Doni Arham; Rila Abdillah; Rima Yulianti; Rizka Amalia (Bajang Institute, 2023)
Stunting is one of the challenges and global nutritional problems globally that are being faced by people in the world. Many efforts have been made to prevent and reduce the incidence of stunting. One of them is by using local food ingredients. This service activity aims to increase the consumption of animal protein by processing local food products, especially beef by diversifying into processed foods that are favored by all groups. The ingredients used in making beef meatballs are fresh beef, tapioca flour, pepper and other spices for flavoring. This Stunting prevention activity began with distributing questionnaires in collaboration with village midwives and then continued with data processing to see the level of stunting in Koto Gunung village then further counseling was carried out to the community, especially mothers and ended with demonstrations and distribution of meatball products as a result of processing local food ingredients to prevent and reduce stunting rates. Based on these results, it can be concluded that through food diversification, beef turns into processed meatballs that are delicious and nutritious.